2020
DOI: 10.1186/s12887-020-02165-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy is an important factor to improve survival in pediatric patients with head and neck rhabdomyosarcoma by enhancing local control: a historical cohort study from a single center

Abstract: Background: The purpose of this study is to analyze the influence of radiation therapy on survival in a historical cohort of 56 pediatric patients with head and neck rhabdomyosarcoma. Methods: A historical cohort of 56 pediatric patients with head and neck rhabdomyosarcoma from June 1st, 2013 to June 30th, 2019 was chosen. Clinical data and follow up results were collected including all diagnosis, treatment and prognosis information. Overall survival (OS) and event free survival (EFS) as time-to-event distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The importance of local control by surgery and/or RT has widely been reported and con rmed in this cohort [8,13,22]. We reported that non-initial RT impairs OS and EFS by causing local failure in this cohort.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The importance of local control by surgery and/or RT has widely been reported and con rmed in this cohort [8,13,22]. We reported that non-initial RT impairs OS and EFS by causing local failure in this cohort.…”
Section: Discussionsupporting
confidence: 53%
“…Radiation therapy (RT) was recommended to all patients except for Group embryonal patients, and RT dose was determined according to the recommendation of Soft Tissue Sarcoma Committee of Children's Oncology Group. As previously stated [13], that in 40% (22/56) of our pediatric HNRMS patients RT was not included as a component of the initial treatment plan, which was mainly attributed to parental refusal due to concerns about long-term RT toxicity or blind con dence in chemotherapy alone.…”
Section: Diagnostic Procedure Risk Strati Cation and Treatment Protocolmentioning
confidence: 91%
See 1 more Smart Citation
“…For some patients with locally advanced, or positive surgical margin diseases, postoperative adjuvant radiotherapy and chemotherapy is usually adopted. Studies have shown that postoperative adjuvant radiotherapy could significantly improve local control [5] and prolong the survival time of patients [9,10]. Adjuvant systemic chemotherapies could improve the prognosis of patients, but their benefits must be weighed against related toxicities [4].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the European approach provides the use of eight cycles of a lower intensity vincristine and actinomycin-D (VA) for a low-risk disease, four cycles of ifosfamide, vincristine, and actinomycin-D (IVA) followed by five cycles of VA for the standard risk disease, nine cycles of IVA are used for a high-risk disease [ 30 ]. RT plays a critical role in the management and local control of RMS [ 33 , 34 ] as also suggested by the fact that omitting RT, the most common protocol deviation, is related to an increased risk of local disease progression and death [ 35 ]. Differences on the indications to RT exist between COG and EpSSG.…”
Section: Introduction To Rhabdomyosarcomamentioning
confidence: 99%